Ultrasonic-assisted extraction of gallic acid and isoquercetin from aspergillus niger fermented tri-phala waste - Teerin Chysirichote; Pattarabhorn Pakaweerachat (My University, 2018)
The Aspergillus niger fermented Tri-phala waste (FTW) was extracted with ultrasonic assisted extraction (UAE) using deionized water as an extraction medium at 30°C. The 40 kHz ultrasonic frequency was used for sonicate the FTW immerged in the water at the ratio of 1 : 100 for 10, 20, 30, 40, 50 and 60 min. The contents of gallic acid, isoquercetin obtained after extraction were measured by HPLC. The extraction yields of gallic acid and isoquercetin were compared with the yields from the water extraction without ultrasonic assistance (control condition). The results showed that using the ultrasonic assistance increased the extraction yield of gallic acid from 0.25±0.03 to 1.26±0.25 g.g -1 with the shorter extraction time from 60 min to 30 min. Moreover, isoquercetin extraction yield increased from 0.17±0.02 to 0.41±0.04 g.g -1 with the shorter extraction time from 60 min to 20 min.
Keywords: Aspergillus niger; Phytochemicals and Antioxidant Activities